Autoimmune and immunogenetic profile of patients with optic neuritis in a population-based cohort - Soelberg, Kerstin; Nilsson, A. C.; Nielsen, C.; Jarius, Sven; Reindl, M.; Wildemann, Brigitte; Lillevang, S. T.; Asgari, N. (Multiple Sclerosis and Related Disorders, 2018)
Background: Optic neuritis (ON) is an inflammatory optic neuropathy, where the genetic and autoimmune dependency remains poorly characterized. Objective: To investigate autoimmune and immunogenetic aspects of ON. Method: In a prospective population-based cohort 51 patients with ON were included. At follow up 20 patients had progressed to multiple sclerosis (MS-ON). All patients were screened for neuronal and systemic autoantibodies. HLA genotypes and allele and genotype frequencies of the PTPN22 C1858T and the PD-1.3 single-nucleotide polymorphisms (SNPs) were determined and compared to a cohort of Danish blood donors, acting as healthy controls. Results: Median follow-up was 366 days (301−430) for MS-ON patients and 375 (range 50-436) for isolated ON (ION). Autoantibodies against myelin oligodendrocyte glycoprotein (MOG-IgG), were positive in two patients, no patients had anti-aquaporin-4 antibodies. Coexisting neural autoantibodies were detected in two patients and in 12 patients other systemic autoantibodies were found. Four (8%) had other autoimmune disorders. A family history of autoimmunity was observed in 12 (24%) and of demyelinating disease in six patients (12%). In MS-ON patients the frequencies of HLA-DQB1*06:02 and HLA-DRB1*15:01 tended to be higher compared to controls (p=0.08). Stratification of patients with presence of oligoclonal bands (OCB) showed an association to the HLA-DQB1*06:02-HLA-DRB1*15:01 haplotype in ION (HLA-DQB1*06:02 and HLA-DRB1*15:01 (p=0.03)), and in MS-ON patients (HLA-DQB1*06:02 and HLA-DRB1*15:01 (p=0.03)). No significant associations to PTPN22 1858C/T or PD-1.3G/A were found in any group comparison. Conclusions: ON patients had a general susceptibility to autoimmunity and two were MOG-IgG positive. HLA-DQB1*06:02 and HLA-DRB1*15:01 were associated with the presence of OCB in ON patients.